Design a Screencast Video for Software Learning in Higher Education (Case Study: Tutorial Video for Digital Illustration Course) - Kharishma, Vidya (JISA(Jurnal Informatika dan Sains), 2020)
In Indonesian higher-education, the lecturer usually teaches software learning to students through a face-to-face practicum at a computer laboratory. However, in some conditions, these learning methods may not be carried out and must be done by online learning methods. Therefore, appropriate learning media are needed to accommodate them. One of the most suitable alternative media is using video with screencasting. A screencast is recordings that show the activity of mouse, tablet, or stylus and the computer screen. Instructional and demonstration videos that must show computer screen activity commonly use screencast technology. This research study the design process and the validation of the use of educational screencast for learning software in higher education. The case study is a screencast video for the Digital Illustration course in the Design of Visual Communication major at Trilogi University. The design methods for developing screencast videos uses the multimedia development model assisted by four-step screen capture processes.  After that, the students enrolled in the Digital Illustration course watch the published video, and then the questionnaire was given to them to see the result of the research. The finding of this research produces some recommendations on how to design a screencast video. A lecturer who considers using screencast to design a learning software tutorial video may consider some recommendations found in this study.